Systematic Literature Review: Pengaruh Ukuran Perusahaan yang Terdata di Bursa Efek Indonesia terhadap Kualitas Audit - Naila Lutfiani; Mia Ayu Putri; Listya Nur Wahida; Fikri Rizki Utama (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to identify the effect of company size on audit quality among firms listed on the Indonesia Stock Exchange. The method used is a Systematic Literature Review (SLR) with a meta-analysis approach applied to relevant articles published between 2018 and 2024. The literature search was conducted through Google Scholar using inclusion criteria consisting of quantitative studies, secondary data, and articles indexed in national Sinta 3 and Sinta 4 journals. Of the 19 articles initially identified, 11 met the selection criteria, and 4 articles were analyzed in depth. The findings indicate that company size has a varying relationship with audit quality depending on firm characteristics, governance mechanisms, the level of oversight, and managerial decisions regarding the selection of independent and professional auditors. In general, large companies tend to choose higher-quality audit services to maintain the credibility, transparency, and reliability of their financial statements. This study concludes that company size is an important factor in explaining audit quality and supporting stakeholder confidence in capital markets. The results also provide useful insights for regulators, investors, auditors, and company management in evaluating audit practices.